PENGEMBANGAN MEDIA AUDIO PODCAST PADA MATA PELAJARAN BAHASA INGGRIS UNTUK SISWA SMA KELAS X - Aulia Rahma Putri; Abna Hidayati; Ulfia Rahmi; Rahmi Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop an audio podcast-based instructional media to improve listening skills in English learning for Grade X senior high school students. The research employs the Research and Development (R&D) method using the Plomp development model, which consists of five stages: preliminary investigation, design, realization, evaluation, and limited implementation. The developed podcast includes interactive narration, practice exercises, and an introduction to Recount Text material. It was produced using BandLab and Eleven Labs and distributed via Spotify. Validation by content and media experts yielded an average score of 4.8 (very valid), while a practicality test involving 40 students resulted in a score of 4.3 (very practical). These findings indicate that audio podcast media is feasible and effective for supporting English language learning, especially in enhancing students’ listening skills.